ANALISIS YURIDIS TINDAK PIDANA NARKOTIKA JENIS BARU BERDASARKAN UNDANG-UNDANG NOMOR 35 TAHUN 2009 TENTANG NARKOTIKA - Adelia Yunita; Mukhlis R; Erdiansyah ' (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2014)
Drug abuse from year to year has increased which ultimately harm the future generation. Along with the development of technology and information, began to appear, a new type of drugs. New narcotics addict who is not registered with the nature and content of legislation in Indonesia. As an example for a real case related new narcotics is indonesian artist Raffi Ahmad begining 2013. Raffi ahmad proven having and using new narcotics addict who is not registeref with the nature nd content of legislation in indonesia, namely derivate chatinone. Declare from bnn that raffi ahmad proven using new narcotics. The purpose of this research are, first to know legal consequences to new type of narcotic crime based law number 35 of 2009, second to know weakness of the sanction assosiated with asas legality. Types of research used in this study is the author of normative legal research. This case study further discusses about the principles of law and comparison of law. Source of data used are secondary data sources obtained from the literature, among others, include official documents, books, research results in the form of reports and so on. The conclusion of the research are, first legal consequences to new type of narcotic crime can not to apply because this type of the new narcotics using addict who is not registeref with the nature nd content of legislation in Indonesia incuding of legislation of narcotics crime based law 35 of 2009. The type narcotics Raffi Ahmad using is known derivative of chatinone, but not include as one type of narcotics in legislation of narcotics crime based law 35 of 2009. Second weakness of the sanction with cas like Raffi Ahmad used is appears legal vacuum, as the result of the appears legal vacuum wiil occur legal uncertainty (rechtsonzekerheid) or legislation uncertanty in society at large further it will occur disorderly law (rechtsverwarring). Advice from the author to the problems studied, first really more than need implementing regulations for narcotics crime based law 35 of 2009, contents really narcotics new type with all of derivative belong type narcotics to avoid the occurrence of appears legal vacum. Second, very expected for sanction of crime but for reahabilitation sanction for healthly society be come true.Keywords: Criminal Offense-Narcotics-Law